Event-Related Potentials Elicited by Face and Face Pareidolia in Parkinson’s Disease - Gulsum Akdeniz; Gonul Vural; Sadiye Gumusyayla; Hesna Bektas; Orhan Deniz (Parkinson's Disease)
Background. Parkinson’s disease is associated with impaired ability to recognize emotional facial expressions. In addition to a visual processing disorder, a visual recognition disorder may be involved in these patients. Pareidolia is a type of complex visual illusion that permits the interpretation of a vague stimulus as something known to the observer. Parkinson’s patients experience pareidolic illusions. N170 and N250 waveforms are two event-related potentials (ERPs) involved in emotional facial expression recognition. Objective. In this study, we investigated how Parkinson’s patients process face and face-pareidolia stimuli at the neural level using N170, vertex positive potential (VPP), and N250 components of event-related potentials. Methods. To examine the response of face and face-pareidolia processing in Parkinson’s patients, we measured the N170, VPP, and N250 components of the event-related brain potentials in a group of 21 participants with Parkinson’s disease and 26 control participants. Results. We found that the latencies of N170 and VPP responses to both face and face-pareidolia stimuli were increased along with their amplitudes, and the amplitude of N250 responses decreased in Parkinson’s patients compared to the control group. In both control and Parkinson’s patients, face stimuli generated greater ERP amplitude and shorter latency in responses than did face-pareidolia stimuli. Conclusion. The results of our study showed that ERPs associated with face and also face-pareidolia stimuli processing are changed in early-stage neurophysiological activity in the temporoparietal cortex of Parkinson’s patients.